2020
DOI: 10.21037/jtd-20-1101
|View full text |Cite
|
Sign up to set email alerts
|

del Nido cardioplegia in surgery for aortic root disease: a historically controlled study

Abstract: Background: To determine the safely and effectively of del Nido cardioplegia (DNC) in surgery for aortic root disease, with mild hypothermic cardiopulmonary bypass (CPB). Methods: From July to December 2017, all patients undergoing the surgery for aortic root disease (total aortic root replacement, valve-sparing aortic root replacement and replacement of aortic valve plus ascending aorta), with mild hypothermic CPB, were retrospectively reviewed at our institution. Patients were divided into two groups based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
2
11
0
2
Order By: Relevance
“…The findings of our study are in line with previously conducted study which states that cardiopulmonary bypass time was statistically significantly shorter in the del Nido group and Del Nido cardioplegia is safe and can be used efficiently in isolated valve replacement surgery. [17][18][19] Our study findings are also supported by recently published systematic review and meta-analysis on del Nido versus blood cardioplegia in adult cardiac surgery. 20 A previous study reported that decreased administration for patients receiving the Del Nido cardioplegia 16 which was inconsistent with this study as we found there was no significant statistical association between the type of cardioplegia and the possibility of receiving the RBCs transfusion.…”
Section: Discussionsupporting
confidence: 87%
“…The findings of our study are in line with previously conducted study which states that cardiopulmonary bypass time was statistically significantly shorter in the del Nido group and Del Nido cardioplegia is safe and can be used efficiently in isolated valve replacement surgery. [17][18][19] Our study findings are also supported by recently published systematic review and meta-analysis on del Nido versus blood cardioplegia in adult cardiac surgery. 20 A previous study reported that decreased administration for patients receiving the Del Nido cardioplegia 16 which was inconsistent with this study as we found there was no significant statistical association between the type of cardioplegia and the possibility of receiving the RBCs transfusion.…”
Section: Discussionsupporting
confidence: 87%
“…Forty-one studies regarding DNC versus CC for myocardial protection used in adult cardiac surgery were included in the final analysis. 7,8,2058 On the basis of 9 retrospective observational studies we had previously included, another 32 studies published after September 2016 were included. Four of these studies were randomized controlled trials (RCTs), 24,36,39,43 one was a prospective observational study 20 while the rest were retrospective observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-eight and 39 studies respectively involving 21,391 and 21,595 patients reported CPB 7,8,2031,33,3542,4458 and ACC time. 7,8,2033,3542,44…”
Section: Resultsmentioning
confidence: 99%
“…V ostatních perioperačních datech nebyl žádný významný rozdíl. 25 S ohledem na chirurgickou revaskularizaci myokardu bychom rádi zmínili dvě velké retrospektivní studie. V roce 2019 publikují Timek a spol.…”
Section: Přehled Literatury -Del Nido V Kardiochirurgii Dospělýchunclassified
“…U nemocných, kde byl použit roztok del Nido, byla pozorována nižší potřeba transfuzních přípravků v perioperačním období. 15 Jiné studie poukazují na rozdílnou potřebu ultrafi ltrace během mimotělního oběhu, 20,25 která je vysvětlena nižším celkovým objemem kardioplegie nebo vyšším podílem krystaloidní složky v něm obsažené.…”
Section: Diskuseunclassified